Entropy-driven binding of octyl gallate in albumin: Failure in the application of temperature effect to distinguish dynamic and static fluorescence quenching - de Carvalho Bertozo, Luiza [UNESP]; Fernandes, Ana J. F. C. [UNESP]; Yoguim, Maurício I. [UNESP]; Bolean, Maytê; Ciancaglini, Pietro; Ximenes, Valdecir F. [UNESP] (My University, 2020)
Fluorescence quenching is widely used to obtain association constants between proteins and ligands. This methodology is based on assumption that ground-state complex between protein and ligand is responsible for quenching. Here, we call the attention about the risk of using the temperature criterion for decision of applying or not fluorescence quenching data to measure association constants. We demonstrated that hydrophobic effect can be the major force involved in the interaction and, as such, superposes the well-established rationalization that host/guest complexation is weakened at higher temperatures due to loss of translational and rotational degrees of freedom. To do so, the complexation of bovine serum albumin with octyl gallate was studied by steady-state, time-resolved fluorescence spectroscopy and isothermal titration calorimetry. The results clearly demonstrated the complexation, even though the Stern-Volmer constant increased at higher temperatures (1.6 × 104 and 4.1 × 105 mol−1 L at 20°C and 40°C), which could suggest a simple dynamic process and not complexation. The entropy-driven feature of the interaction was demonstrated by the unfavorable enthalpy (∆H° = 104.4 kJmol−1) but favorable entropy (∆S° = 447.5 Jmol−1 K−1). The relevance of the ligand hydrophobicity was also evaluated by comparing ascorbic acid and its ester ascorbyl palmitate. Docking simulations showed a higher number of hydrophobic contacts and lower energy poses for the esters, confirming the experimental results. In conclusion, the well-established rationalization that host/guest complexation is weakened at higher temperatures is not straightforward for protein-ligand interactions. Hence, the temperature effect for a decision between static and dynamic quenching and its use to decide if a complexation at ground state is taking place between ligand and protein should not be used.
Keywords: albumin; ascorbic acid; ascorbyl palmitate; entropy; fluorescence quenching; hydrophobic effect; octyl gallate